Amphiphilic thickeners for personal care
By using the fine particle structure of water-soluble polymer coated with silicone in cosmetics, the problem of moisture and stickiness of cosmetics is solved, the durability and ultraviolet blocking performance of cosmetics are improved, and an efficient production process is achieved.
Patent Information
- Application Number
- CN202410847064.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-28
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-03
AI Technical Summary
When existing cosmetic thickeners improve makeup durability and ultraviolet blocking, they can easily lead to a decrease in moisture and an increase in viscosity, and have low production efficiency, making it difficult to improve moisture and stability at the same time.
Using polymers based on the microparticle structure of Korean registered patent No. 10-2531603, the core part uses a water-soluble polymer and the shell part is coated with silicone polymer. The crosslinked polymer is prepared through polymerization to form two spherical fine particles. A viscous thickener that enhances water retention and reduces stickiness.
It achieves increasing moisture in cosmetics, improving stickiness and contamination, while improving makeup durability and UV blocking durability, and improving production efficiency.
Smart Images

Figure CN119241779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thickener that can be used in personal care compositions or products such as cosmetics, and more particularly to a thickener that can impart a moist feel while having a low greasy feel. Background Art
[0002] When applying makeup or using sunscreen products, the important attribute is the high durability of makeup or UV blocking, so even if applied once, the makeup effect will last for a long time without the need for touch-up or reapplication. However, in order to improve the durability of makeup, a water-in-oil (W / O) formulation with excellent water resistance to sweat and sebum resistance to sebum is used, so there is a disadvantage of reduced moisture and dryness. In addition, due to the volatile oil used for rapid setting when applied to the skin, the formability of the formulation will also decrease when manufacturing the product, which becomes a reason for reducing production efficiency.
[0003] To solve this problem, if the proportion of water phase in the formulation is increased, the stability of the formulation is hindered due to the characteristics of the water-in-oil formulation, and phase separation is likely to occur. If more emulsifiers are used to enhance the stability of the formulation, a vicious cycle of increased stickiness will occur. In addition, if film formers are used to increase the durability of makeup, stickiness and staining will also increase.
[0004] Therefore, there is a need for a technology that can increase the feeling of moisture and improve the stickiness and staining feeling while improving the durability of makeup and UV blocking.
[0005] In order to solve this problem, the inventors discovered a polymer with a fine particle structure based on the previously studied Korean registered patent No. 10-2531603, used a polymer capable of absorbing water and maintaining viscosity in the core portion, and chemically coated a silicone polymer in the shell portion to inhibit the evaporation of water in the core portion, thereby increasing the moisture feeling. At the same time, the silicone polymer in the shell portion improves the makeup durability and the sticky and staining feeling, thereby completing the present invention.
[0006] Prior art literature
[0007] Patent Literature
[0008] Korean registered patent No. 10-2531603 Summary of the invention
[0009] Issues to be resolved
[0010] The object of the present invention is to provide an amphiphilic thickener for personal care that can increase moisture and improve stickiness and staining.
[0011] Another object of the present invention is to provide a cosmetic material comprising the amphiphilic thickener of the present invention and having excellent makeup durability and ultraviolet light blocking durability.
[0012] Solution to the problem
[0013] In order to achieve the above object, the amphiphilic thickener of the present invention comprises a crosslinked polymer obtained by polymerizing a water-soluble monomer represented by the following Chemical Formula 1, a crosslinkable monomer, and a silicone-containing monomer represented by the following Chemical Formula 2.
[0014] [Chemical formula 1]
[0015]
[0016] In the above formula,
[0017] R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, wherein m=1 to 3,
[0018] R2 is -OX, NH2 or -NH-R3-SO3Y,
[0019] R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-,
[0020] X and Y are H + 、Na + , Li + , K + or NH3 + , and X and Y may be identical to each other,
[0021] [Chemical formula 2]
[0022]
[0023] In the above formula,
[0024] m is an integer from 1 to 5,
[0025] n is an integer from 10 to 5000,
[0026] R1 is hydrogen or C 1-3 alkyl,
[0027] R2 is hydroxyl, C 1-3 Alkyl or vinyl.
[0028] In one specific example, in order to prepare the above-mentioned amphiphilic thickener, the present invention includes a method for preparing a crosslinked polymer by dissolving and heating the water-soluble monomer represented by the above-mentioned chemical formula 1, the crosslinkable monomer and the silicone-containing monomer represented by the above-mentioned chemical formula 2, and then adding a reaction initiator to carry out a polymerization reaction.
[0029] In a specific example, the method for preparing an amphiphilic thickener of the present invention may include: preparing an oil-in-water emulsion composition comprising an aqueous phase containing a water-soluble monomer and a crosslinkable monomer represented by the above chemical formula 1 and an oil phase containing a silicone-containing monomer represented by the above chemical formula 2 and a non-polar organic solvent; preparing an oil-in-water reverse emulsion composition by heating to above 60° C.; and preparing a crosslinked polymer by adding a reaction initiator to perform a polymerization reaction.
[0030] In a specific example, as a method for preparing the amphiphilic thickener, a PIT (phase inversion temperature) polymerization method may be used.
[0031] In another specific example, the method for preparing an amphiphilic thickener of the present invention may include: dissolving the water-soluble monomer represented by the above chemical formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by the above chemical formula 2 in an alcohol solvent; heating to above 60° C.; and preparing a crosslinked polymer by adding a reaction initiator to perform a polymerization reaction. As the method for preparing the amphiphilic thickener, a precipitation polymerization method may be used.
[0032] In a specific example, the method for preparing the amphiphilic thickener may further include a step of obtaining the thickener in a solid form, for example, by using a precipitation method using a non-solvent for the cross-linked polymer.
[0033] Effects of the Invention
[0034] In the present invention, a thickener in the form of homogeneous fine particles can be provided, the core of which is composed of a water-soluble polymer crosslinked body and the surface of which is coated with a silicone polymer. Therefore, the thickener in the form of spherical particles of the present invention has the advantages of maintaining the form of particles even when swelling in a water phase, and enhancing the water retention capacity by the coated silicone polymer as the shell part. In addition, the spherical particles coated with a silicone polymer on the surface also have high dispersibility in the oil phase, which contributes to the durability of makeup, and has the effect of reducing stickiness and staining due to the spherical polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 : is an exemplary diagram showing a method for preparing an amphiphilic thickener according to the inverse emulsion polymerization method in the present invention.
[0036] Figure 2 is an exemplary diagram showing a method for preparing an amphiphilic thickener according to a precipitation polymerization method in the present invention.
[0037] Figure 3 This is a graph showing the results of confirming the water-retaining capacity of the amphiphilic thickener according to the present invention.
[0038] Figure 4 This is a photograph showing the results of confirming the staining feeling of the cosmetic formulation to which the amphiphilic thickener according to the present invention was applied.
[0039] Figure 5 This is a graph showing the results of confirming the stickiness of the sunscreen formulation using the amphiphilic thickener according to the present invention. DETAILED DESCRIPTION
[0040] However, the present invention can be subjected to multiple changes and can have various forms, so the specific embodiments and explanations described below are only to help understand the present invention, and are not intended to limit the present invention to a specific disclosed form. It should be understood that the scope of the present invention covers all changes, equivalents and even substitutes included in the thought and technical scope of the present invention.
[0041] Hereinafter, the present invention will be described in more detail.
[0042] In the present invention, "thickener" refers to a cross-linked polymer prepared according to the preparation method of the present invention, and may refer to a solution in which the cross-linked polymer is dispersed. In particular, the thickener may refer to a substance generally used in a personal care composition or personal care product for the purpose of increasing viscosity.
[0043] In one specific example, the amphiphilic thickener of the present invention includes a cross-linked polymer obtained by polymerizing a water-soluble monomer and a cross-linkable monomer represented by the following Chemical Formula 1 and a silicone-containing monomer represented by the following Chemical Formula 2.
[0044] In a specific example, the water-soluble monomer may be a compound of the following Chemical Formula 1.
[0045] [Chemical formula 1]
[0046]
[0047] In the above formula,
[0048] R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, wherein m=1 to 3,
[0049] R2 is -OX, NH2 or -NH-R3-SO3Y,
[0050] R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-,
[0051] X and Y are H + 、Na + , Li + , K + or NH3 + , and X and Y may be identical to each other,
[0052] [Chemical formula 2]
[0053]
[0054] In the above formula,
[0055] m is an integer from 1 to 5,
[0056] n is an integer from 10 to 5000,
[0057] R1 is hydrogen or C 1-3 alkyl,
[0058] R2 is hydroxyl, C 1-3 Alkyl or vinyl.
[0059] In a specific example, the method for preparing an amphiphilic thickener of the present invention may include the steps of preparing an oil-in-water emulsion composition comprising an aqueous phase containing a water-soluble monomer and a crosslinkable monomer represented by the above chemical formula 1 and an oil phase containing a silicone-containing monomer represented by the above chemical formula 2 and a non-polar organic solvent (step 1-1); preparing a water-in-oil inverse emulsion composition by heating to above 60° C. (step 1-2); and preparing a crosslinked polymer by adding a reaction initiator to conduct a polymerization reaction (step 1-3).
[0060] In a specific example, as a method for preparing the above-mentioned amphiphilic thickener, a PIT (phase inversion temperature) polymerization method can be used. In the PIT polymerization method, when the temperature is low as in step 1-1, an oil-in-water emulsion composition is formed, and then the temperature is increased in step 1-2, thereby converting it into an oil-in-water inverse emulsion composition.
[0061] In the present invention, the above step 1-1 is a step of preparing an oil-in-water emulsion composition comprising an aqueous phase containing a water-soluble monomer and a crosslinkable monomer represented by the above chemical formula 1 and an oil phase containing a silicone-containing monomer represented by the above chemical formula 2 and a non-polar organic solvent.
[0062] In the present invention, the aqueous phase in step 1-1 comprises the water-soluble monomer represented by the chemical formula 1 and a cross-linkable monomer.
[0063] In a specific example, the water-soluble monomer represented by Chemical Formula 1 in step 1-1 can be at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide and polyethylene glycol acrylate.
[0064] Specifically, the water-soluble monomer represented by the above Chemical Formula 1 may be a compound represented by the following Chemical Formula 1a.
[0065] [Chemical formula 1a]
[0066]
[0067] In the present invention, the content of the water-soluble monomer represented by Chemical Formula 1 in the above step 1-1 is not particularly limited, but for example, it may include 10 to 99 weight percent, preferably 30 to 95 weight percent, and more preferably 50 to 95 weight percent, relative to 100 weight percent of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2. Within the above range, the stability of the composition is more stable, and the effect of improving the stickiness can be more excellent.
[0068] In a specific example, the crosslinkable monomer of step 1-1 can be a compound having two or more acrylate groups, two or more acrylamide groups, or two or more vinyl groups. As such a crosslinkable monomer, for example, one or more selected from the group consisting of ethoxylated trimethylolpropane triacrylate (TMPETA), trimethylolpropane triacrylate (TMPTA), methylenebisacrylamide, divinyl sulfone, divinylbenzene, divinyl ether, divinyl acetylene, polyethylene glycol diacrylate, polyethylene glycol triacrylate, and four-arm polyethylene glycol tetraacrylate can be used.
[0069] In a specific example, the crosslinkable monomer in step 1-1 can more preferably be ethoxylated trimethylolpropane triacrylate (TMPETA), trimethylolpropane triacrylate (TMPTA) or a combination thereof. The crosslinkable monomer is a compound having more than three crosslinking points, which can increase the molecular weight of the crosslinked product, thereby increasing the viscosity.
[0070] In the present invention, the content of the crosslinkable monomer in the above step 1-1 is not particularly limited, but for example, the content of the crosslinkable monomer may include 0.01 to 20 wt %, preferably 0.1 to 10 wt %, and more preferably 0.5 to 5.0 wt %, relative to 100 wt % of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2. Within the above range, the stability of the composition is more excellent or the effect of improving the stickiness can be more excellent.
[0071] In a specific example, the solvent of the aqueous phase in step 1-1 can be water (distilled water).
[0072] In a specific example, the pH of the aqueous phase in step 1-1 is not particularly limited, but may be, for example, 5 to 9. The pH may be adjusted using a common pH adjuster, such as aqueous ammonia.
[0073] In the present invention, the oil phase in step 1-1 may include the silicone-containing monomer represented by the chemical formula 2 and an organic solvent.
[0074] In the present invention, the content of the silicone-containing monomer represented by Chemical Formula 2 in the above step 1-1 is not particularly limited, but for example, it may include 1 to 70% by weight, preferably 5 to 60% by weight, and more preferably 10 to 50% by weight, relative to 100% by weight of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer, and the silicone-containing monomer represented by Chemical Formula 2. Within the above range, the stability of the composition is more excellent or the effect of improving the stickiness can be more excellent.
[0075] In a specific example, the organic solvent may be a non-polar organic solvent, specifically C 6-17 Hydrocarbon oil, which can be C 6-17 Straight-chain saturated hydrocarbon oil. When the carbon number is outside the above range, the production efficiency in the polymerization reaction may decrease.
[0076] In a specific example, as the above-mentioned non-polar organic solvent, heptane can be used. The boiling point of heptane is 98°C, which is not limited in the polymerization process according to the present invention compared with other organic solvents. During the process, during the initiator input process, heat is generated due to the explosive reaction, and there is a danger that the internal temperature of the reactor increases by about 5 to 10°C. The method of slowly inputting the initiator in order to maintain the steady state of the reaction temperature has the disadvantage of increasing the process time and thus increasing the production unit price when applied to a large-scale production process. In addition, if heated to above the boiling point, the reactant will explode (bumping), resulting in an increased risk of reactor explosion, so the reaction heat management is a very important factor during mass production. Therefore, in the present invention, by using heptane as an organic solvent, the thickener for the purpose of the present invention can be easily prepared without being restricted by the process.
[0077] In the present invention, the oil phase in step 1-1 may further contain a surfactant.
[0078] In a specific example, as the surfactant of the above step 1-1, more than one surfactant can be used. The total HLB value of the above surfactant can be 6 to 14, 7 to 10 or 8 to 9. At this time, for the total HLB value, when one surfactant is used, it refers to the HLB value of the above surfactant, and when two or more surfactants are used, it can refer to the sum of the HLB values of the two or more surfactants. When the above total HLB value is 6 or less, due to the strong hydrophobicity of the surfactant, it exists as an oil-in-water type reverse emulsion from room temperature, thereby polymerizing without a phase inversion process, so the effect of reducing the emulsion size may not be sufficient. In addition, when the total HLB value is 14 or more, due to the strong hydrophilicity of the surfactant, the water-in-oil emulsion in which the external phase is the water phase is maintained, so that spherical particles are not formed, so there is a concern that the amorphous state of the prepared thickener increases.
[0079] In one specific example, two surfactants can be used as the surfactant in step 1-1. In this case, a surfactant having an HLB value of 3 to 8 and a surfactant having an HLB value of 8 to 16 can be used in combination, or a surfactant having an HLB value of 5 to 7 and a surfactant having an HLB value of 9 to 11 can be used in combination.
[0080] In a specific example, as the surfactant in step 1-1, polyoxyethylene (3) oleyl ether (HLB = 6.6) and polyoxyethylene (6) oleyl ether (HLB = 9.6) can be used in combination. Specifically, polyoxyethylene (3) oleyl ether (HLB = 6.6) and polyoxyethylene (6) oleyl ether (HLB = 9.6) can be used in combination at a weight ratio of 1:1, and the HLB value can be 8.1.
[0081] Specifically, by appropriately combining two surfactants with an HLB value of 3 to 8 and two surfactants with an HLB value of 8 to 16, or two surfactants with an HLB value of 5 to 7 and two surfactants with an HLB value of 9 to 11, a polymerization reaction can be carried out in a uniform reverse emulsion phase with a small particle size by using a PIT (phase inversion temperature) polymerization method that is an oil-in-water (o / w) emulsion phase at room temperature but is converted into a water-in-oil (w / o) emulsion phase at a certain temperature or above. Thus, in the present invention, a thickener in the form of homogeneous spherical fine particles can be prepared.
[0082] The thickener in the form of spherical fine particles polymerized in the above manner has the following advantages: the thickener not only maintains the particle form even when swelling in a water phase, but also has uniform particle dispersion, transparent appearance, and high stability.
[0083] In a specific example, the content of the above-mentioned surfactant in the above-mentioned step 1-1 is not particularly limited, but may be changed according to the type of organic solvent. Specifically, the content of the above-mentioned surfactant may be 5 to 30% by weight relative to 100% by weight of the total of pure water, organic solvent, surfactant, water-soluble monomer represented by Chemical Formula 1, crosslinkable monomer, and silicone-containing monomer represented by Chemical Formula 2. Within the above content range, the phase inversion of the emulsion can be performed, and PIT polymerization can be easily performed.
[0084] In a specific example, the weight ratio of the water phase to the oil phase in step 1-1 can be 30:70 to 70:30. Within the above range, the composition can be more stable or the effect of improving the stickiness can be more excellent.
[0085] In the present invention, the above step 1-2 is a step of preparing a water-in-oil type reverse emulsion composition by heating to 60° C. or higher. The heating in the above step 1-2 can be performed at 50° C. to 80° C., preferably 55° C. to 75° C., and when the temperature is heated to less than 50° C., there is a problem that the phase transition phenomenon of the emulsion is difficult to occur.
[0086] In a specific example, the emulsion prepared in the above step 1-1 of the present invention has an oil-in-water type at room temperature, but can be phase-inverted into an oil-in-water type emulsion through the above step 1-2. The emulsion generated by the above phase inversion can have an effect of reducing the size of the emulsion, and can have an effect of adjusting the particle size of the polymer prepared in the following step to be smaller.
[0087] In a specific example, the reaction temperature of step 1-2 may be, for example, above 62° C., above 65° C., above 70° C. or 75° C., and the upper limit may be 100° C. Within the above temperature range, the thickener can be prepared more stably.
[0088] In the present invention, the above steps 1-3 are steps of preparing a cross-linked polymer by adding a reaction initiator to carry out a polymerization reaction.
[0089] In a specific example, the type of reaction initiator in the above steps 1-3 is not particularly limited to a common free radical polymerization initiator, but can be selected from the group consisting of peroxides and azo compounds, etc. As the above peroxide initiator, benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cumyl hydroperoxide, hydrogen peroxide or potassium persulfate can be used, and as the azo compound initiator, azo nitrile, azo ester, azo amide, azo imidazoline, azo amidine, macro azo initiator, etc. can be used. In the present invention, it is preferred to use an azo compound initiator, and more preferably 4,4′-azobis(4-cyanovaleric acid) is used, which may be advantageous in terms of polymerization reaction efficiency.
[0090] In the present invention, after preparing the reverse emulsion, by adding an initiator and performing a reaction, a cross-linked polymer having the viscosity of the present invention, that is, a thickener, can be obtained, and the yield of the thickener can be increased.
[0091] In a specific example, the reaction temperature of the above steps 1-3 may be above 62° C., above 65° C., above 70° C. or 75° C., and the upper limit may be 100° C. Within the above temperature range, the thickener can be prepared more stably.
[0092] In a specific example, the above steps 1-3 can be carried out for a reaction time of 1 to 12 hours, preferably 2 to 6 hours.
[0093] In another specific example of the present invention, the method for preparing the amphiphilic thickener of the present invention may include: dissolving the water-soluble monomer represented by the above chemical formula 1, the crosslinkable monomer and the silicone-containing monomer represented by the above chemical formula 2 in an alcohol solvent (step 2-1);
[0094] A step of heating to above 60° C. (step 2-2); and
[0095] A step of preparing a cross-linked polymer by performing a polymerization reaction by adding a reaction initiator (step 2-3).
[0096] In a specific example, as the preparation method of the amphiphilic thickener, in particular, the polymerization method can use precipitation polymerization. The water-soluble monomer of Chemical Formula 1, the silicone-containing monomer of Chemical Formula 2, the crosslinkable monomer and the reaction initiator used in the precipitation polymerization method can be the same as those used in the PIT polymerization method.
[0097] In a specific example, the alcohol solvent used as the solvent may be C 2-8 Alcohols. The reaction yield can be further improved within the above range.
[0098] In the present invention, the solution formed by the cross-linked polymer prepared by the above-mentioned preparation method can be used as a thickener. In addition, a thickener in a solid form such as powder can be finally prepared by sedimenting the above-mentioned solution with a sedimentation agent. In this case, a sedimentation agent non-solvent can be used, and acetone can be used in particular.
[0099] In addition, the present invention provides a thickener prepared by the thickener preparation method.
[0100] Figure 1 1 is an exemplary diagram of a method for preparing a polymer thickener according to the present invention (steps 1-1 to 1-3).
[0101] The thickener according to the present invention can be obtained by Figure 1 The spherical thickener was prepared in the same manner.
[0102] The thickener according to the present invention can be obtained by Figure 2 The spherical thickener was prepared in the same manner.
[0103] The thickener according to the present invention has a spherical fine particle form and swells in water, ethanol or a water-ethanol mixed solution, thereby being able to provide a high-viscosity solution that is visually uniform in appearance.
[0104] The thickener prepared according to the present invention may have an average particle size of 10 to 300 um.
[0105] In addition, the viscosity of the thickener prepared in the present invention in a 1% (w / v) aqueous dispersion at 25° C. may be 500 to 150,000 cPs, or 5000 to 100,000 cPs.
[0106] The present invention is described in more detail below by way of implementation / comparative examples. These examples are only used to illustrate the present invention, and the scope of the present invention is not limited to these examples.
[0107] [Example]
[0108] Comparative Example 1.
[0109] Aqueous phase: 17 g of acrylamido methylpropanesulfonic acid and 0.5 g of trimethylolpropane ethoxylatetriacrylate were dissolved in 63 g of distilled water, and then neutralized to pH 7-9 with ammonia water.
[0110] Oil phase: 10 g of each of polyoxyethylene (3) oleyl ether and polyoxyethylene (6) oleyl ether were added into 80 g of heptane and mixed thoroughly.
[0111] The aqueous phase and the oil phase were placed in a reactor and heated to 70° C., and then 0.1 g of an initiator 4,4′-azobis(4-cyanovaleric acid) was added and reacted for 3 hours. The thickener was precipitated with acetone and dried to obtain a product.
[0112] Comparative Example 2
[0113] Aqueous phase: 17 g of acrylamidomethylpropane sulfonic acid and 0.5 g of trimethylolpropane ethoxylate triacrylate were dissolved in 63 g of distilled water, and then neutralized to pH 7-9 with ammonia water.
[0114] Oil phase: a certain amount of silicone methacrylate (molecular weight: 5,000) was put into 80 g of heptane and mixed thoroughly.
[0115] The aqueous phase and the oil phase were placed in a reactor and heated to 70° C., and then 0.1 g of an initiator 4,4′-azobis(4-cyanovaleric acid) was added and reacted for 3 hours. The thickener was precipitated with acetone and dried to obtain a product.
[0116] In this case, the reaction performed without an emulsifier did not result in a uniform reaction, and a gel was formed in a form that was difficult to use for the test, so it seemed that emulsion polymerization using an emulsifier was required.
[0117] Examples 1 to 3.
[0118] Aqueous phase: 17 g of acrylamidomethylpropane sulfonic acid and 0.5 g of trimethylolpropane ethoxylate triacrylate were dissolved in 63 g of distilled water, and then neutralized to pH 7-9 with ammonia water.
[0119] Oil phase: A certain amount of silicone methacrylate (molecular weight: 1,000 / 5,000 / 10,000) was added to 80 g of heptane, and 10 g of polyoxyethylene (3) oleyl ether and polyoxyethylene (6) oleyl ether were added respectively and mixed thoroughly.
[0120] The aqueous phase and the oil phase were placed in a reactor and heated to 70° C., and then 0.1 g of an initiator 4,4′-azobis(4-cyanovaleric acid) was added and reacted for 3 hours. The thickener was precipitated with acetone and dried to obtain a product.
[0121] Table 1 below shows the compositions.
[0122] [Table 1]
[0123]
[0124] Comparative Example 3.
[0125] 20 g of acrylamidomethylpropanesulfonic acid and 1 g of trimethylolpropane ethoxylate triacrylate were added to 100 g of t-butanol, and then 6.4 g of ammonia water was added, and stirred for 30 minutes to completely dissolve.
[0126] The mixture was heated to 70° C., and 0.3 g of an initiator 4,4′-azobis(4-cyanovaleric acid) was added to react for 3 hours. The thickener was precipitated with ethanol and acetone, and dried to obtain a solution.
[0127] Example 4
[0128] 20 g of acrylamidomethyl propane sulfonic acid and 1 g of trimethylolpropane ethoxylate triacrylate were added to 100 g of t-butanol, and then 6.4 g of ammonia water was added and stirred for 30 minutes to completely dissolve. Next, a certain amount of silicone methacrylate (molecular weight: 5,000) was added and mixed thoroughly.
[0129] The mixture was heated to 70° C., and 0.3 g of an initiator 4,4′-azobis(4-cyanovaleric acid) was added to react for 3 hours. The thickener was precipitated with ethanol and acetone, and dried to obtain a solution.
[0130] Table 2 below shows the respective compositions (unit: g).
[0131] [Table 2]
[0132]
[0133] Experimental Example 1. Comparison of water retention capacity ( Figure 3 )
[0134] 1 g of each thickener prepared with the composition of Comparative Examples 1 and 3 and Examples 1 to 4 was dissolved in 99 g of distilled water. Thereafter, 10 g of the polymer solution at 55°C was transferred to a petri dish and placed in an oven. The weight of the sample was measured over time to confirm the amount of water evaporation. The results are shown in Figure 3 middle.
[0135] The results, such as Figure 3 As shown, the thickeners of Examples 1 to 4 have a significantly longer water retention time than Comparative Examples 1 and 3. This means that when silicone is applied, the evaporation of water in the polymer core containing water is suppressed, thereby improving the moisturizing power.
[0136] Experimental Example 2: Comparison of the staining feeling when applying makeup cosmetics
[0137] First, as shown in Table 3 below, a color cosmetic formulation was prepared.
[0138] First, the raw materials corresponding to the oil phase were mixed and heated to 80° C. to be melted. During this time, the water phase was added and dissolved, and then the water phase was added to the oil phase and homogenously mixed at 5000 rpm for 10 minutes to prepare a dosage form.
[0139] 30 μl of each prepared formulation was dropped on a marble floor, spread thinly to a thickness of 25 μm, and then dried for 4 hours. 10 μl of each artificial sebum was dropped on the dried formulation, left at room temperature for 10 minutes, and then covered with artificial leather, and force was applied by moving a 200 g weight back and forth 10 times. The covered artificial leather was removed, and the amount of color cosmetics stained on the leather was visually compared. The results are shown in Figure 4 middle.
[0140] [Table 3]
[0141]
[0142] like Figure 4 As shown in the figure, it is confirmed that the higher the molecular weight of the polymer synthesized with silicone methacrylate, the less staining the color cosmetics show. In the case of not using a polymer, the color cosmetics have almost no sebum resistance, and in the case of not coating the polymer with silicone methacrylate, the color cosmetics have a high level of staining. It is estimated that this is because as the dosage form solidifies (setting), the silicone coated on the surface of the spherical polymer adheres to each other between the polymers to form a film, thereby showing sebum resistance and water resistance.
[0143] Experimental Example 3: Comparison of stickiness during application of makeup products
[0144] 10 μl of each color cosmetic of Experimental Example 2 was dropped on artificial leather, spread at 2×2 (cm), and then the stickiness according to the drying time was measured. A cylindrical applicator was used as a texture analyzer, and the measurement parameters were set to a measurement rate of 1 mm / s and a measurement force of 1.0 g, and the stickiness was calculated based on the negative energy when the applicator first contacted the dry dosage form. The results are shown in Table 4 below.
[0145] [Table 4]
[0146] Makeup 1 Makeup 2 Makeup 3 Makeup 4 Makeup 5 Makeup 6 Sticky feeling (gf·s) 14.4 16.5 12.1 8.6 6.5 6.7
[0147] As shown in Table 4, it was confirmed that when a general water-dispersible polymer was used, the stickiness was very strong, but when silicone methacrylate was used, the stickiness was less. If a water-dispersible polymer is used to solve the dry feeling of a makeup product, the dry feeling is reduced but the stickiness increases. Therefore, in order to reduce the stickiness while maintaining the moisture, this can be solved by using a spherical polymer coated with silicone methacrylate.
[0148] Experimental Example 4. Comparison of stickiness when applying UV blocking cosmetics
[0149] First, as shown in Table 5 below, an ultraviolet blocking cosmetic formulation was prepared.
[0150] First, the raw materials corresponding to the oil phase were mixed and heated to 80° C. to be melted. During this time, the water phase was added and dissolved, and then the water phase was added to the oil phase and homogenously mixed at 4000 rpm for 10 minutes to prepare a dosage form.
[0151] 3 μl of each UV blocking cosmetic (sunscreen) was dropped onto artificial leather, and then the stickiness was measured according to the number of times the applicator touched. A spherical applicator was used as a texture analyzer, and the measurement parameters were set to a measurement rate of 1 mm / s, a measurement force of 1.0 g, repeated 200 times, and the stickiness was calculated based on the negative energy when the applicator touched the dosage form. The results are shown below Figure 5 middle.
[0152] [Table 5]
[0153]
[0154] like Figure 5As shown in the figure, it was confirmed that when general polymers were used, the stickiness was very strong, but when silicone methacrylate was used, the stickiness was less. In order to maintain the moisture in UV blocking products and reduce the stickiness, as in makeup products, this can be solved by using spherical polymers coated with silicone methacrylate.
[0155] Experimental Example 5. Comparison of UV blocking performance and durability when UV blocking cosmetics are applied
[0156] 33.5 μg of the sunscreen of Experimental Example 4 was thinly spread on a PMMA plate (PMMA plate) (Helioplate, Helioscreen, France) of 5×5 (cm) size for measuring the ultraviolet blocking index. After 15 minutes, the initial ultraviolet blocking value (SPF) was measured using an invitro measuring instrument. After 4 hours, 10 μg of artificial sebum was dropped on the PMMA plate (PMMA plate) coated with the sunscreen and spread, and the SPF value was measured again after 10 minutes to confirm the SPF change. The results are shown in Table 6 below.
[0157] [Table 6]
[0158]
[0159] As shown in the above results, it was confirmed that the SPF reduction rate was smaller when the spherical thickener coated with silicone methacrylate was used than when the sunscreen made of general polymer was used. This shows that, similar to the previous Experimental Example 2, the sebum resistance shown in color cosmetics is also applicable to UV blocking cosmetics as is, thereby improving the sustainability of UV blocking performance.
[0160] Experimental Example 6. Actual use test of stickiness and moisture feeling when using skin lotion dosage form
[0161] First, as shown in Table 7 below, a keratin management toner formulation was prepared.
[0162] Twenty women aged 25 to 50 were selected as subjects and the toner formulation was applied on their faces once a day for three days. After application, a questionnaire survey was conducted on the feeling of use. The feeling of use was evaluated based on the criteria of "◎: 16 or more of the 20 subjects said that it was not sticky or had a high moisture feeling, ○: 12 to 15 of the 20 subjects said that it was not sticky or had a high moisture feeling, △: 8 to 11 of the 20 subjects said that it was not sticky or had a high moisture feeling". The results are shown in Table 7 below.
[0163] [Table 7]
[0164] Ingredient name (unit weight %) Toner 1 Toner 2 Toner 3 Toner 4 Toner 5 Purified water Up to 100 Up to 100 Up to 100 Up to 100 Up to 100 Dexpanthenol 0.500 0.500 0.500 0.500 0.500 1,2-Hexanediol 4.000 1.000 1.000 1.000 1.000 Dipropylene glycol 8.000 8.000 8.000 8.000 8.000 Xanthan gum 0.400 0.400 0.400 0.400 0.400 Example 2 - 0.25 0.5 - - Example 4 - - - 0.25 0.5 Gluconolactone 3.000 3.000 3.000 3.000 3.000 lactic acid 3.000 3.000 3.000 3.000 3.000 total 100.000 100.000 100.000 100.000 100.000 Not too sticky △ ○ ◎ ○ ◎ Moisture feeling ○ ○ ◎ ○ ◎
[0165] From the results shown in Table 7, it can be seen that the keratin management ingredient in the keratin management formulation has a high stickiness, but when the polymer provided by the present invention is used, the stickiness is reduced and the moisture feeling is increased.
Claims
1. An amphiphilic thickener comprising a crosslinked polymer obtained by polymerizing a water-soluble monomer and a crosslinkable monomer represented by Chemical Formula 1 with a silicone-containing monomer represented by the following Chemical Formula 2: [Chemical formula 1] In the above formula, R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, wherein m=1 to 3, R2 is -OX, NH2 or -NH-R3-SO3Y, R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-, X and Y are H + 、Na + , Li + , K + or NH3 + , and X and Y may be identical to each other, [Chemical formula 2] In the above formula, m is an integer from 1 to 5, n is an integer from 10 to 5000, R1 is hydrogen or C 1-3 alkyl, R2 is hydroxyl, C 1-3 Alkyl or vinyl.
2. The amphiphilic thickener according to claim 1, wherein The water-soluble monomer represented by the above Chemical Formula 1 includes at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide, and polyethylene glycol acrylate.
3. The amphiphilic thickener according to claim 1, wherein The water-soluble monomer represented by the above chemical formula 1 is a compound represented by the following chemical formula 1a: [Chemical formula 1a] 4. A method for preparing an amphiphilic thickener, comprising: The step of preparing an oil-in-water emulsion composition comprising an aqueous phase containing a water-soluble monomer and a crosslinkable monomer represented by the following chemical formula 1 and an oil phase containing a silicone-containing monomer represented by the following chemical formula 2 and a non-polar organic solvent; A step of preparing a water-in-oil type inverse emulsion composition by heating to above 60° C.; and Steps for preparing a cross-linked polymer by polymerization reaction by adding a reaction initiator: [Chemical formula 1] In the above formula, R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, wherein m=1 to 3, R2 is -OX, NH2 or -NH-R3-SO3Y, R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-, X and Y are H + 、Na + , Li + , K + or NH3 + , and X and Y may be identical to each other, [Chemical formula 2] In the above formula, m is an integer from 1 to 5, n is an integer from 10 to 5000, R1 is hydrogen or C 1-3 alkyl, R2 is hydroxyl, C 1-3 Alkyl or vinyl.
5. A method for preparing an amphiphilic thickener, comprising: The step of dissolving a water-soluble monomer represented by the following chemical formula 1, a cross-linkable monomer, and a silicone-containing monomer represented by the following chemical formula 2 in an alcohol solvent; The step of heating to above 60°C; and Steps for preparing a cross-linked polymer by polymerization reaction by adding a reaction initiator: [Chemical formula 1] In the above formula, R1 is -H, -CH3, -CH2CH3 or -(CH2) m CH3, wherein m=1 to 3, R2 is -OX, NH2 or -NH-R3-SO3Y, R3 is -(CH2)-, -(CH2)2-, -(CH2)3-, -(CH2)4-, -(CH2)2(CH3)2- or -(CH2)3CH3-, X and Y are H + 、Na + , Li + , K + or NH3 + , and X and Y may be identical to each other, [Chemical formula 2] In the above formula, m is an integer from 1 to 5, n is an integer from 10 to 5000, R1 is hydrogen or C 1-3 alkyl, R2 is hydroxyl, C 1-3 Alkyl or vinyl.
6. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The water-soluble monomer represented by the above Chemical Formula 1 includes at least one selected from the group consisting of acrylamidomethylpropanesulfonic acid (AMPS), acrylic acid, acrylamide, and polyethylene glycol acrylate.
7. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The water-soluble monomer represented by the above chemical formula 1 is a compound represented by the following chemical formula 1a: [Chemical formula 1a] 8. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The water-soluble monomer represented by Chemical Formula 1 is contained in an amount of 50 to 95 wt % relative to 100 wt % of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer and the silicone-containing monomer represented by Chemical Formula 2.
9. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The crosslinkable monomer is a compound having two or more acrylate groups, two or more acrylamide groups, or two or more vinyl groups.
10. The method for preparing an amphiphilic thickener according to claim 4, wherein: The above non-polar organic solvent is C 6-17 Hydrocarbon oil.
11. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The content of the silicone-containing monomer represented by Chemical Formula 2 is 5 to 50 wt % relative to 100 wt % of the total of the water-soluble monomer represented by Chemical Formula 1, the crosslinkable monomer and the silicone-containing monomer represented by Chemical Formula 2.
12. The method for preparing an amphiphilic thickener according to claim 4, wherein: The oil phase further comprises one or more surfactants, and the total HLB value of the above surfactant combination is 6 to 14.
13. The method for preparing an amphiphilic thickener according to claim 12, wherein: As the surfactant, two types of surfactants, a surfactant having an HLB value of 3 to 8 and a surfactant having an HLB value of 8 to 16, are used.
14. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The reaction initiator is one or more selected from the group consisting of peroxides and azo compounds.
15. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The above polymerization reaction is carried out at a temperature above 60°C for 2 to 6 hours.
16. The method for preparing an amphiphilic thickener according to claim 5, wherein: The above alcohols are C 2-8 Alcohols.
17. The method for preparing an amphiphilic thickener according to claim 4 or 5, wherein: The method further comprises the step of obtaining the thickener in a solid form by sedimentation using a sedimentation agent.
